Absence of Potentiation with Murine Antiplatelet GPIIb/IIIa Antibody of Thrombolysis with Recombinant Tissue-Type Plasminogen Activator (rt-PA) in a Canine Venous Thrombosis Model - Spriggs, D; Gold, H K; Hashimoto, Y; Houtte, E Van; Vermylen, J; Collen, D (Thrombosis and Haemostasis, 1989)
F(ab’)2 fragments of a murine monoclonal anti-platelet GPIIb/ IIIa antibody (7E3) are a potent platelet aggregation inhibitor, which in a canine coronary artery thrombosis model accelerate lysis with recombinant tissue-type plasminogen activator (rt-PA) and prevent reocclusion (7).In the present study, we have investigated the potential value of platelet aggregation inhibition as adjunctive therapy to lysis of venous thrombi, by measuring the thrombolytic potency of 7E3- F(ab’)2 and rt-PA used alone or in combination, in dogs with a 125I-fibrin labeled femoral vein thrombus. The dose-response of thrombolysis with rt-PA infused over 4 hours was linear: doses of 0.075 mg/kg, 0.15 mg/kg and 0.3 mg/kg produced 37 ± 3, 57 ± 11 and 83 ± 4% lysis respectively, against a background value of 20 ± 2%. With F(ab’)2 fragments of 7E3 given as a bolus of 1.2 mg/ kg, which saturated 70% of the platelet GPIIb/IIIa receptors and prolonged the bleeding to more than 30 min, lysis was not significantly increased over background. Combination of 0.3 or 0.6 mg/kg of 7E3-F(ab’)2 with either 0.03 or 0.06 mg/kg of rt-PA did not produce more lysis than obtained with a comparable dose of rt-PA alone. No significant changes in plasma fibrinogen or α2- antiplasmin were observed with either agent alone or with the combination. It is concluded that extensive inhibition of platelet aggregation does not potentiate the thrombolytic effect of rt-PA in this venous thrombosis model.
Keywords: Recombinant tissue-type plasminogen activator (rt-PA); Platelet inhibition; Thrombolysis